Analysis of Bad Credit or Non-Performing Loan (NPL) at PT Bank Negara Indonesia (Persero) Tbk - Khesya Sabilah Rizwinie; Andreas Martin Raja Sirait; Fihi Khoirani Sihotang; Patricya Damanik (Asian Journal of Management Analytics, 2023)
Bad credit is an important thing in the banking world because it affects the financial health of banks. This study aims to analyze the level of bad credit at PT Bank Negara Indonesia (Persero) Tbk in terms of the Non-Performing Loan (NPL) ratio. The method used in this research is qualitative. The data obtained is secondary data with quantitative data obtained from the annual report of PT Bank Negara Indonesia (Persero) Tbk for the last 15 years, starting from 2007–2022. The results of this study indicate that the highest NPL ratio level was 8.2% in 2007, and the lowest was 1.9% in 2018. The average NPL from 2007 to 2022 was 4.9%, which was included in the healthy criteria and did not endanger the bank.